Case Report: Mevalonate kinase deficiency: an underdiagnosed cause of ischemic stroke—characterization of a novel genetic variant - Hamidi, Lyna-Nour; Drda, Jack Christopher; Belhocine, Meriem; Elfassy, Hannah-Laure; Ducharme-Bénard, Stéphanie; Chayer-Lanthier, Maxime; Sultana, Bushra; Lanthier, Sylvain (Frontiers in Immunology, 2025)
Mevalonate kinase deficiency (MKD) is an inherited autoinflammatory syndrome resulting from impaired isoprenoid biosynthesis due to biallelic mevalonate kinase (MVK) mutations. This metabolic defect leads to dysregulated innate immunity, particularly excessive interleukin-1β release. While typically presenting in childhood with periodic fevers, expanding evidence links MKD to heterogeneous adult phenotypes with immune-mediated end-organ damage. We report an adult male presenting with leg pain and finger cyanosis followed by acute ischemic stroke, macular rash, and lymphadenopathies. He exhibited classical markers of innate immune activation, including persistent elevation of C-reactive protein. Genetic testing identified compound heterozygosity for the known MVK pathogenic variant c.1129G>A (V377I) and a novel missense variant, c.1049A>C (Q350P). Structural modeling of Q350P revealed disruption of the GHMP kinase domain, predicted to destabilize mevalonate kinase conformation and impair its function. The measurement of mevalonate kinase activity in lymphocytes was at 55% (normal >60%). Interleukin-1β blockade with canakinumab was initiated, and the blood markers of inflammation normalized, further supporting a central role for innate immune dysregulation. This case highlights a novel MVK missense variant (Q350P) with subnormal mevalonate kinase activity. The patient’s compound heterozygous state with partially preserved mevalonate kinase activity may explain the attenuated systemic features and the delayed clinical onset. Remarkably, ischemic stroke was part of the initial presentation, suggesting that mevalonate kinase deficiency can manifest primarily through thrombo-inflammatory complications in adulthood, even in the absence of recurrent febrile episodes. This expands the phenotypic spectrum of MKD and underscores the need to consider adult-onset autoinflammatory syndromes in the differential diagnosis of cryptogenic ischemic strokes with markers of systemic inflammation. It also supports the utility of cytokine-targeted therapies in such contexts.